2022
DOI: 10.31590/ejosat.1045487
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Meta-Analysis of Aflatoxin B1 Presence in Red Pepper

Abstract: Aflatoxins are one of the pollutants that can be isolated from the dried food products, especially spices. Since red pepper is one of the most consumed spices all over the world, this research aimed to estimate the prevalence and concen-tration of aflatoxin B1 (AFB1) in different red pepper spices with the help of a systematic review and meta-analysis. Therefore, the articles published between January 2000 and December 6, 2020, were systematically collected from four well-known databases. In this context, 10 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…For the first four samples, the detected AFB1 concentrations have deviated from EU standards ( 155 ). Indeed, according to the outcomes of a recent meta-analysis on the occurrence of AFB1 in red pepper, the prevalence of AFB1 among studied samples was 50.8%, respectively ( 156 ). This study reported that the minimum and maximum concentrations of AFB1 were detected in Korean and Turkey samples in the concentration of 0.14 and 31.13 mg/kg, respectively ( 156 ).…”
Section: Afs Contaminants In Spices and Medicinal Herbsmentioning
confidence: 99%
“…For the first four samples, the detected AFB1 concentrations have deviated from EU standards ( 155 ). Indeed, according to the outcomes of a recent meta-analysis on the occurrence of AFB1 in red pepper, the prevalence of AFB1 among studied samples was 50.8%, respectively ( 156 ). This study reported that the minimum and maximum concentrations of AFB1 were detected in Korean and Turkey samples in the concentration of 0.14 and 31.13 mg/kg, respectively ( 156 ).…”
Section: Afs Contaminants In Spices and Medicinal Herbsmentioning
confidence: 99%
“…Apart from these four aflatoxins, aflatoxins M1 and M2 were isolated from the milk and urine of lactating mammals fed with aflatoxin feed. Plant-based foods contain the most aflatoxin B1, B2, G1 and G2 types (CAST 2003;Oner et al, 2022;Sevdin et al, 2021). It has been determined that aflatoxin M1 and M2 species are found in directly consumed animal products such as meat, milk and eggs (Desjardins et al, 2003;Magan & Olsen 2004).…”
Section: Introductionmentioning
confidence: 99%